THE ADVANTAGES OF USING YOUTUBE ANIMATION VIDEOS IN LEARNING ARABIC VOCABULARY FOR GRADE IV STUDENTS AT MIS BINA SANTRI MEDAN - Rahmadani, Rahmadani; Al Anshory, Abdul Muntaqim; Hasaniyah, Nur (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2024)
This research discusses YouTube video animation as a learning medium how the utilization of YouTube video animation as a learning medium in improving the Arabic vocabulary of class IV students of MIS Bina Santri Medan. Given the important role of media in supporting the success of the process and the achievement of expected learning outcomes, teachers should fully understand it as an integral part of the learning process in madrasah and is one aspect that must be of concern to teachers. The approach used in this research is a descriptive qualitative approach. Data collection methods were conducted through interviews, observations and documentation through class IV teachers of MIS Bina Santri Medan. Data analysis was carried out using the Miles and Huberman method, namely data reduction, data presentation and conclusion drawing. The results showed that using YouTube animated videos in vocabulary learning made it easier for teachers to convey material to students. Learning activities become more active, interesting and interactive so as to foster student motivation and interest in learning and have a positive impact on student vocabulary mastery. Audio visual media is very effective in learning at the MI level because in addition to cognitive it is also a stimulus for students' psychomotor.